MEMAKNAI PERINTAH ṢADAQAH DALAM ALQURAN PADA TATARAN KEHIDUPAN MODERASI BERAGAMA (Telaah Makna Lafaz Ṣadaqah dalam Ayat Alquran) - Maria Ulfah Syarif; Husaini Husaini; Muh. Qodri Syarif Ilham (IAIN BONE, 2022)
AbstractSadaqah is anact that is mentioned the acknowledgment in the world, both in the Qur'an and Hadith. Dueto the fadhilah and wasilah of sadaqah, the recommendation to share and give sadaqah is contained in the verses of the Qur'an approximately 39 verses. Because the practice of sadaqah is not only worship that teaches a person to have a good relationship with Allah (hablūmīnallah) but also brings the mutaṣaddiq to have good relations with fellow humans (hablumīnannās). After the implementation of social distancing dueto the Covid-19 pandemic, the advice to share and give sadaqah is becoming in creasingly widespread in Indonesia, which is famous for the plurality of its population in terms of ethnic and religion. Without knowing the time, offers to give sadaqah are milling on all social media homepages. Not even a few individuals or institutions dare to offer an suggestion to give sadaqah directly to personal contacts. So now, anyone and anywhere from all walksoflife has the opportunity to give sadaqah or receive sadaqah. This paper will dig deeper into what the Qur'an means when it says that a religiously moderate person should give sadaqah. This study aims to gather research data from different kinds of literature and focus its analysis on the world of texts, specifically on what the commandment sadaqah in the verses of the Qur'an says about living a religiously moderate life. Furthermore, the results show that the command to sadaqah is not only material but also canbe non-material. Hence, every Muslim has the opportunity to give sadaqah. Giving sadaqah is not only to fellow Muslims but also permissible to give charity to non-Muslims (sadaqah Tatawwu' or al-sadaqah al-Nafilah). AbstarakSedekah merupakan sebuah amalan yang disebutkan balasannya di dunia, baik dalam Alquran maupun Hadis. Begitu besarnya fadhilah dan wasilah sedekah, sehingga anjuran berbagi dan bersedekah tertuang dalam ayat-ayat Alquran kurang lebih sebanyak 39 ayat. Wajar saja, karena amalan sedekah bukan hanya sebatas ibadah yang mengajarkan seseorang untuk memiliki hubungan baik dengan Allah (hablūmīnallah) namun juga membawa si mutaṣaddiq memiliki hubungan baik dengan sesama manusia (hablumīnannās). Pasca pemberlakuan sosial distancing akibat pandemi Covid-19, fenomena ajakan berbagi dan bersedekah semakin marak di Indonesia yang tersohor dengan kemajemukan penduduknya baik dari segi ras maupun agama. Tanpa mengenal waktu, tawaran bersedekah tersebar di semua beranda media sosial. Bahkan tidak sedikit orang ataupun lembaga yang berani menawarkan ajakan bersedekah langsung ke kontak pribadi. Sehingga kini, siapapun dan dimanapun semua lapisan masyarakat berpeluang untuk bersedekah maupun menerima sedekah. Tulisan ini bertujuan untuk mengkaji lebih mendalam makna anjuran sedekah pada Alquran dalam hubungannya dengan kehidupan moderasi beragama.Penelitian ini berusaha menghimpun data penelitian dari berbagai literatur dan menjadikan dunia teks sebagai obyek utama analisisnya yaitu menelaah makna perintah ṣadaqah dalam ayat-ayat Alquran dalam hubungannya dengan kehidupan moderasi beragama. Dan hasilnya menunjukkan bahwasanya perintah berṣadaqah tidak melulu dengan materi melainkan bisa pula berbentuk non materi sehingga setiap umat muslim berpeluang untuk memberikan ṣadaqah. Pemberian ṣadaqah pun tidak hanya kepada sesama muslim melainkan dibolehkan pula bersedekah kepada non muslim (al-Ṣadaqah Taṭawwu’ atau al-Ṣadaqah al-Nafilah).